The application of electrolytic in-process dressing to precision grinding processes - Zervos, Charilaos (Cranfield University, 2007)
Electrolytic In-Process Dressing (ELID) has attracted a lot of attention in recent years as it is a promising method of grinding a wide range of materials, including ones that are difficult to machine, to high quality finishes. The EC funded project Nanogrind undertook the construction of a high precision grinding machine which will incorporate an ELID system, applying the technique on a spherical wheel for the production of components with intricate geometries (e.g. freeforms, aspherics). In this project, the main objective was to understand the basic features of ELID, such as the electrochemical properties of the oxide layer and its effect on the final finish of the produced components (glass, a hard and brittle material was the main focus). Acoustic emission studies, a promising in-process monitoring tool, verified the effectiveness of ELID grinding when the contact area between the wheel and workpiece is increased. Compared to conventional resin bond wheel grinding, ELID ground components were of higher quality with less damage introduced in them. ELID current monitoring also gave excellent results when it was correlated to surface finish achieved across the surface of the testpieces ground. Electrochemical Impedance Spectroscopy was an innovative technique that was applied in order to acquire basic information about the metal bond wheel, such as the charge transfer resistance. Its correlation to the oxide layer thickness gave an indication of the way corrosion rates change with the presence or not of an oxide film on the wheel surface. Finally, sub-surface damage introduced into glass components was evaluated and was compared to the depths of damage predicted by theoretical models, giving further insight into the way the overall processing time of a component should be optimised in order to acquire high quality, damage-free finished components in a time efficient, cost effective way.